Construction of netlike 3D Z-scheme photoelectrodes with improved photocatalytic performance based on g-C3N4 nanosheets modified TiO2 nanobelt-tubes. (23rd November 2020) - Ma, Xiaohan; Chen, Qinghua; Liu, Guocheng; Zhou, Yuanming; Ma, Dong; Xin, Shuaishuai; Yu, Chengze; Zhang, Bin; Xin, Yanjun
Graphical abstract: Highlights: Network 3D Z-scheme g-C3 N4 nanosheets/TiO2 nanobelt-tubes photoelectrodes was synthesized. The TiO2 nanobelt-tubes structure improved the transfer efficiency of electrons. Z-scheme heterostructure facilitated the separation of photogenerated electron hole pairs. g-C3 N4 /TNBTs heterostructure exhibited stronger photocatalytic degradation of TC. Abstract: Netlike 3D Z-scheme graphitic carbon nitride (g-C3 N4 ) nanosheets decorated TiO2 nanobelt-tubes (TNBTs) photoelectrodes (g-C3 N4 /TNBTs) were fabricated via anodization and coating technology. The network 3D photoelectrodes were characterized by HR-TEM, XPS and UV–Vis/DRS. The photoelectrochemical properties were examined to reveal the transfer and separation efficiency of photogenerated electrons. The photocatalytic activity was investigated by the photocatalytic decomposition of tetracycline hydrochloride (TC) under light irradiation. Results showed that g-C3 N4 with rugged surface were loaded on TNBTs by chemical bond joint to form heterostructure. The g-C3 N4 /TNBTs exhibited stronger visible light absorption and reduced recombination of photogenerated electron-hole pairs than TNBTs. The photocurrent response of g-C3 N4 /TNBTs was 1.88-fold that of TNBTs. The photocatalytic rate of g-C3 N4 /TNBTs for TC was significantly higher than that of TNBTs (0.017 min −1 vs 0.007 min −1 ). The O2 − and h + were the dominant oxidation species during the degradation of TC. The possible photocatalytic mechanism of constructing Z-scheme heterojunction was also proposed.